Analysis of Brayton Cycle Efficiency at 100 MW Load Before and After Overhaul of Unit 1 Block 1 At PLTGU PT. PLN Nusantara Power Up Gresik - Muhammad Ridwan; Fahri Wibisono (Asian Journal of Social and Humanities, 2024)
Electricity is one of the most important needs in everyday life due to technological advances. So various efforts are needed to increase electricity production, one way is to build a power plant that can produce productive electricity so that this happens, one way to determine electricity productivity is the value of cycle efficiency. If the value of the cycle efficiency is higher in a generator, then the PLTG performance will be maximized. And if the cycle efficiency value gets smaller, it can be said that the PLTG's performance is not good. Therefore, to maintain PLTG performance, it is necessary to carry out an overhaul to maintain optimal PLTG performance. In this study using cycle efficiency to determine the increase in efficiency before and after overhaul at a load of 100 MW and the causes, after analyzing the efficiency of the brayton cycle increased from 41% to 42%, the cause was a decrease in turbine efficiency from 74 to 91% and compressor efficiency from 73 to 82% after overhaul the increase affected fuel consumption so that the requirement of kcal/kwh decreased to 3196.4 kcal/ Kwh